2022
DOI: 10.2147/rmhp.s347401
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Risk Nomogram Model for Perioperative Respiratory Adverse Events in Children Undergoing Airway Surgery: An Observational Prospective Cohort Study

Abstract: The aim of this study was to explore the associated risk factors of perioperative respiratory adverse events (PRAEs) in children undergoing airway surgery and establish and validate a nomogram prediction model for PRAEs. Patients and Methods: This study involved 709 children undergoing airway surgery between November 2020 and July 2021, aged ≤18 years in the affiliated hospital of Xuzhou Medical University. They were divided into training (70%; n = 496) and validation (30%; n = 213) cohorts. The least absolute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 46 publications
(76 reference statements)
0
10
0
Order By: Relevance
“…Machine learning was the most represented with 38 included studies describing its use, 13 23 28 29 31 32 , 34 , 35 , 36 , 38 , 39 , 40 , 42 44 46 47 , 49 , 50 , 51 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 70 whereas two applications incorporated the use of fuzzy logic 21 , 22 and only one study described the use of each of natural language processing 23 and computer vision. 13 Many branches of machine learning were discussed, including regression models, 29 45 46 49 50 51 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 decision trees, 23 , 33 , 34 , 35 expert systems, …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Machine learning was the most represented with 38 included studies describing its use, 13 23 28 29 31 32 , 34 , 35 , 36 , 38 , 39 , 40 , 42 44 46 47 , 49 , 50 , 51 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 70 whereas two applications incorporated the use of fuzzy logic 21 , 22 and only one study described the use of each of natural language processing 23 and computer vision. 13 Many branches of machine learning were discussed, including regression models, 29 45 46 49 50 51 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 decision trees, 23 , 33 , 34 , 35 expert systems, …”
Section: Resultsmentioning
confidence: 99%
“… 13 Many branches of machine learning were discussed, including regression models, 29 45 46 49 50 51 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 decision trees, 23 , 33 , 34 , 35 expert systems, 59 K-means classifiers, 35 K-nearest neighbours, 29 , 44 Bayesian approaches, 29 neural networks, 23 , 25 , 34 , 45 random forest models, 23 29 31 , 45 , 46 , 47 and support vector machines. 34 , 45 , 70 Regression models were the most commonly described, with one study describing a linear regression model, 50 23 studies describing logistic regression models, 29 36 46 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , …”
Section: Resultsmentioning
confidence: 99%
“…Bias-corrected calibration curve showed that the model could accurately predict the occurrence of RAEs during transport when the observed probability of RAEs during transport was less than 40%. Inversely, a few existing models that cannot accurately and objectively predict RAEs during anesthesia induction or perioperative period, and do not include a special type of surgery such as interventional cardiac catheterization (8,(30)(31)(32). Based on the clinical data of 19,095 pediatric patients undergoing elective ambulatory anesthesia for surgery and radiology, Subramanyam et al developed and validated a risk prediction model for the occurrence of RAEs from the onset of anesthesia induction until discharge from the PACU, with a Cstatistic of 0.64 (8).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies looked at predictive models to prevent desaturation <95%, laryngospasm, bronchospasm, prolonged cough, airway obstruction, stridor, pneumonia, atelectasis, pneumothorax and pyrexia have been performed as well [17][18][19]. Similarly, decision trees and K-means classifiers were used to develop an Automated Unsupervised Respiratory Event Analysis (AUREA) model to classify breathing patterns obtained through dual belt respiratory inductance plethysmography (RIP) in infants [20].…”
Section: Andandmentioning
confidence: 99%